1992
DOI: 10.1172/jci115847
|View full text |Cite
|
Sign up to set email alerts
|

Induction of heme oxygenase is a rapid, protective response in rhabdomyolysis in the rat.

Abstract: Heme proteins such as myoglobin or hemoglobin, when released into the extracellular space, can instigate tissue toxicity. Myoglobin is directly implicated in the pathogenesis of renal failure in rhabdomyolysis. In the glycerol model of this syndrome, we demonstrate that the kidney responds to such inordinate amounts of heme proteins by inducing the heme-degradative enzyme, heme oxygenase, as well as increasing the synthesis of ferritin, the major cellular repository for iron. Prior recruitment of this response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
558
0
6

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 655 publications
(587 citation statements)
references
References 22 publications
(32 reference statements)
23
558
0
6
Order By: Relevance
“…Although plasma hemoglobin and heme-binding proteins such as haptoglobin, hemopexin, and albumin are able to prevent the liberation and toxicity of heme, excessive release of hemoprotein will presumably saturate these buffering systems, allowing heme to enter endothelial cells. This is the case in rhabdomyolysis, a disease in which Nath et al (30) have demonstrated that HO-1 induction provides protection to tissues presumably through the subsequent increases in Ft and bilirubin. Ischemia-reperfusion injury will also bring about significant intravascular hemolysis (31,32), again supplying substrate for HO.…”
Section: Discussionmentioning
confidence: 99%
“…Although plasma hemoglobin and heme-binding proteins such as haptoglobin, hemopexin, and albumin are able to prevent the liberation and toxicity of heme, excessive release of hemoprotein will presumably saturate these buffering systems, allowing heme to enter endothelial cells. This is the case in rhabdomyolysis, a disease in which Nath et al (30) have demonstrated that HO-1 induction provides protection to tissues presumably through the subsequent increases in Ft and bilirubin. Ischemia-reperfusion injury will also bring about significant intravascular hemolysis (31,32), again supplying substrate for HO.…”
Section: Discussionmentioning
confidence: 99%
“…Haem oxygenase is the ratelimiting enzyme in haem degradation to CO, iron and biliverdin, the latter being converted into bilirubin by biliverdin reductase [3]. The proposed antioxidant role for HO-1 is based on some crucial experimental observations : (i) HO-1 gene expression is extremely sensitive to up-regulation by oxidative stress in a variety of mammalian tissues [2,[4][5][6] ; (ii) induction of HO-1 protein or transfection of cells with the HO-1 gene protect tissues against oxidant-mediated injury [7][8][9][10] ; and (iii) HO-1 knockout mice exhibit reduced stress defences when exposed to oxidative challenge [11]. Since biliverdin and bilirubin have been shown to possess potent antioxidant properties [12] and upregulation of HO-1 is usually accompanied by increased levels of ferritin, a protein which sequesters intracellular catalytic iron [13], HO-1 appears to be an excellent candidate for cytoprotection.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments with HO-2 knock-out mice reveal the accumulation of iron in the lung after hyperoxic exposure ; this occurs without the induction of ferritin [24]. Indeed, the protective effects attributed to HO might actually reside in the induction of ferritin, rather than in HO-1 itself, as was seen in a rodent rhabdomyolysis model [12]. Similar findings have been confirmed in endothelial cells, where it was the induction of ferritin and not HO up-regulation that protected cells against the toxicity of H # O # [23].…”
Section: Figure 5 Hne Formationmentioning
confidence: 97%
“…Test incubations contained 100 µl of Hb (0.1 mg\ml, final concentration) in place of buffer. Hb has been used previously in studies with HO [12,20]. It might not be the ultimate form of haem utilized by the enzyme in i o but it is definable, readily soluble and biologically relevant.…”
Section: Conditions Of Incubationmentioning
confidence: 99%
See 1 more Smart Citation